2020
DOI: 10.1002/jcp.30177
|View full text |Cite
|
Sign up to set email alerts
|

Zinc finger E‐box binding homeobox 1 and atherosclerosis: New insights and therapeutic potential

Abstract: Zinc finger E-box binding homeobox 1 (ZEB1), an important transcription factor belonging to the ZEB family, plays a crucial role in regulating gene expression required for both normal physiological and pathological processes. Accumulating evidence has shown that ZEB1 participates in the initiation and progression of atherosclerotic cardiovascular disease. Recent studies suggest that ZEB1 protects against atherosclerosis by regulation of endothelial cell angiogenesis, endothelial dysfunction, monocyteendothelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 158 publications
0
7
0
2
Order By: Relevance
“…Сердечно-сосудистые заболевания (ССЗ) представляют собой основной фактор инвалидизации и преждевременной смерти во всем мире [1]. По данным Всемирной организации здравоохранения, на ССЗ приходится более 17 млн смертей в год, и по прогнозам, этот показатель к 2030 г. превысит 23 млн [2,3].…”
Section: Review введениеunclassified
“…Сердечно-сосудистые заболевания (ССЗ) представляют собой основной фактор инвалидизации и преждевременной смерти во всем мире [1]. По данным Всемирной организации здравоохранения, на ССЗ приходится более 17 млн смертей в год, и по прогнозам, этот показатель к 2030 г. превысит 23 млн [2,3].…”
Section: Review введениеunclassified
“…The activator of KLF2 presented anti-inflammatory effects and attenuated the adhesion of monocytes to endothelial cells, which could be a promising therapeutic strategy for atherosclerosis [ 53 ]. Other ZFPs, such as KLF14, zinc finger E-box binding homeobox 1 (ZEB1), and early growth response gene-1 (Egr-1), also participate in the regulation of atherogenesis [ 54 , 55 , 56 ].…”
Section: Zinc-related Proteinsmentioning
confidence: 99%
“…VSMCs in the plaque exhibit a co-expression of both VSMC- and macrophage-specific biomarkers, and the concomitant macrophage properties, such as secreting pro-inflammatory molecules and inducing the migration of inflammatory cells [ 104 , 106 ]. These findings indicate a potential dual role of VSMCs in atherogenesis, and zinc might influence the progress by regulating the function of transcription factors containing zinc-finger structures, such as KLF4 and ZEB1 [ 55 , 81 , 108 ].…”
Section: Zinc and Atherogenic Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiovascular diseases (CVDs) represent the major factor of disability and premature death worldwide. Recently, the World Health Organization (WHO) revealed that CVD accounts for > 17 million deaths per year and this figure will rise to over 23 million by the year 2030 (GBD 2015 Risk Factors Collaborators 2016 ; Li et al 2021a ). It is well known that atherosclerosis is an inflammatory disease of the vascular wall, which is recognized as the underlying basis of many CVDs, such as hypertension, myocardial infarction, stroke, and peripheral arterial disease.…”
Section: Introductionmentioning
confidence: 99%